Effect of socio-economic characteristics on fertility and under-five mortality: examples from the Santals of Birbhum district, West Bengal, India - Malakar Biswanath; Roy Subrata K. (Anthropological Review, 2017)
Fertility and under-five mortality are considered as key health indicators of a population. Both the fertility and under-five mortality varies accross countries, regions, ethnic groups and so on, which may bedue to disparities in socio-economic and cultural factors. The study aimed to better understanding the association of fertility and under-five mortality with selected socio-economic characteristics of the Santal labourer group of Birbhum district, West Bengal. Cross-sectional data have been collected on fertility, mortality and socio-economic characteristics from 627 ever-married Santal women. Descriptive statistics, multivariate logistic regression and Cox proportion hazard analysis have been done. Total fertility rate (TFR) of the present study group was 2.9 and the mortality rate was 105.1. In the present study, educational status, age and household size of the women have significant association with fertility. Under-five mortality has significant association with educational status of mother and birth order of the children. The study indicated that education was the one of the important factors (socio-economic characters) that had most significant impact on both fertility and under-five mortality of the Santal labourer group.